AB0119 Deregulated Expression of Mirnas in Purified Disease Relevant Blood Cell Populations in Patients with Spondyloarthritis. (15th July 2016) - Tost, J.; Bugge Tinggaard, A.; Wang-Renault, S.-F.; Busato, F.; Dougados, M.; Miceli-Richard, C.
Abstract : Background: MiRNAs have been shown to play a critical role in the regulation of both the innate and the adaptive components of the immune system. Deregulated miRNA expression has been found in different inflammatory and autoimmune diseases and may have anti- or pro-inflammatory activities based on their specific target mRNAs. Altered miRNA expression has been detected in several inflammatory diseases such as inflammatory bowel disease (IBD) and psoriasis. Although a few studies concerning correlation between Spondyloarthritis (SpA) and miRNA have been published, no systematic studies in specific cell populations have been reported so far. Moreover, a recently published computational analysis (1) showed a large overlap of active gene regulatory regions with genetic variation associated with SpA for CD4 T cells and CD14 monocytes. Objectives: This study aimed to analyze the miRNA expression pattern in these two disease relevant cell populations of purified CD4 T cells and CD14 monocytes from SpA patients and controls. Methods: SpA patients were monocentrically recruited between October 2014 and May 2015 in the department of rheumatology (Cochin hospital). These patients had an active disease despite NSAIDs intake and were eligible for a TNF-blocker treatment. The mean BASDAI (± SD) was 53.2±23.7; ASDAS 3.2±1.1 and CRP 13±16.6 mg/L. Among these patients, 23 fulfilled the ASAS classification criteria (imaging arm) with sacro-iliitis on X-rays (n=16) or objective signs of inflammation on MRI (n=21). Only one patient fulfilled the clinical arm. We first analyzed the expression of 360 MiRNAs in cell-sorted (MACS) monocytes and CD4 T-lymphocyte populations from these SpA patients and 16 age and sex-matched controls by qPCR using the Exiqon MicroRNA Ready-to-Use Human Panel I on the miRNA-enriched fraction from both CD4+ and CD14+ cell populations. Results: In CD4 cells 6 miRNAs were found to be differentially expressed including miR-491-3p, recently reported to be downregulated in ulcerative colitis, and miRNA-26a, a well know inflammation associated miRNA implicated in both allergic inflammation and autoimmune diseases. In monocytes, 25 miRNAs were found to be differentially expressed including the paradigmatic anti-inflammatory miRNA miR-146a and as the most significantly expressed miRNA, a miRNA involved in the degradation of TNFα. Conclusions: The study is the first to analyze miRNA expression in purified disease-relevant blood cell populations in SpA bringing into evidence a number of interesting miRNAs whose deregulation might contribute to the pathogenesis of the disease. Integration with RNA expression data will allow the functional impact of the miRNA expression changes patterns in the blood cell populations allowing to better understand the molecular changes in SpA and potentially identify novel targets for therapeutic intervention. The validation of 10 differentially expressed miRNAs by qPCR-based assays in additional samples of monocytes and CD4 lymphocytes from independent 12 patients and 12 controls is ongoing. References: Farh et al. Nature (2015) Acknowledgement: This work was funded by a SIRIUS Research Grant from UCB Pharma S.A. Disclosure of Interest: J. Tost Grant/research support from: UCB Pharma S.A., A. Bugge Tinggaard: None declared, S.-F. Wang-Renault: None declared, F. Busato: None declared, M. Dougados: None declared, C. Miceli-Richard Grant/research support from: UCB Pharma S.A.